Gelatin films plasticized with a simulated biodiesel coproduct stream (eXPRESS Polymer Letters)
In order to explore the possibility of substituting an unrefined biodiesel coproduct stream (BCS) for refined glycerol as a polymer plasticizer we have prepared cast gelatin films plasticized with a simulated BCS, i.e., mixtures of glycerol and some of the typical components found in BCS (methyl linoleate, methyl oleate, linoleic acid, and oleic acid). We measured the tensile properties as a function of plasticizer composition, and analyzed the specific effect of each individual component on tensile properties. We found that it is the unrecovered alkyl esters that largely determine the tensile properties, and that BCS can be successfully used to plasticize cast gelatin films as long as the BCS contains 11 parts by weight, or less, of unrecovered alkyl esters per 100 parts glycerol.